Cervical human papilloma virus (HPV) DNA primary screening test: Results of a population-based screening programme in central Italy. (September 2017) - Passamonti, Basilio; Gustinucci, Daniela; Giorgi Rossi, Paolo; Cesarini, Elena; Bulletti, Simonetta; Carlani, Angela; Martinelli, Nadia; Broccolini, Massimo; D'Angelo, Valentina; D'Amico, Maria Rosaria; Di Dato, Eugenio; Galeazzi, Paola; et al.
Objective: To present the results of the first and second round human papilloma virus (HPV)-based screening programme in the Umbria region after three years. Methods: From August 2010 to November 2011, the entire female population aged 35–64 in a local health district was invited for HPV testing (HPV-DNA cobas4800 on a liquid-based cytology sample). HPV-negative women were re-invited after three years. For HPV-positive women, a slide was prepared and interpreted. Positive cytologies were referred to colposcopy; negatives were referred to repeat HPV after one year. If HPV was persistently positive, women were referred to colposcopy; if negative, to normal screening. Indicators of the first and second round are compared with those of cytology screening in the same area in the preceding three years. Results: Participation was 56.5%, the same as cytology (56.6%). HPV-positivity was 6.4% (396/6272), cytology triage positivity was 35.6%; 251 cytology negative women were referred to one-year HPV retesting, 84.1% complied, and 55.5% were positive. Total colposcopy referral was 4.1%, and for cytology 1%. The detection rate for cervical intraepithelial neoplasia grade 2 or more severe was 10‰, compared with 3.7‰ using cytology. After three years, HPV-positivity was 3.4% (129/3831), overall colposcopy referral was 2.3% (most at one-year follow-up), and detection rate was 0.5/1000. Conclusions: The first round detection rate was more than twice that of cytology screening, while colposcopy referral increased fourfold. At the second round, the detection rate decreased dramatically, showing that longer interval and more conservative protocols are needed.